Impact of Technological Development on Human Cognitive Functioning - Ramos-Galarza, Carlos (2024)
Human beings have several cognitive functions (memory, attention, language, perception, executive functions and others) that allow them to perform all their daily activities. In the context of the stimulation of human cognitive functions, classic activities based on tangible resources such as pencil and paper have been developed. In this context, there is an opportunity for technological development to make proposals to create games that stimulate human mental abilities. In this context, this article reports a quantitative systematic review of research about games to cognitive stimulation. Among the main results obtained, games that stimulate skills such as perception, attention, memory, executive functions, psychomotor skills and information processing speed were identified. The following are some of the results processed in this systematic review.